Soleh Adi Pramono: A Malangese Mask Puppet Dalang (1951-Present) - Arining Wibowo; Juanda; Siane Herawati; Basrin Melamba; Genya Anuceni Kurnain (Pascasarjana ISBI Bandung Conference Series, 2025)
The Malangese Mask Puppet art has given birth to a number of famous dalangs and artists, including Mbah Reni from Polowijen and Mbah Karimun from Kedungmonggo, whose invaluable contributions to the development and sustainability of the traditional art are not to be questioned. Soleh Adi Pramono from Gladahdowo, manager of Padepokan (Art Center) Mangun Dharmo, is also a dalang who continues the life-long project of his predecessors, namely to preserve the Malangese Mask Puppet art. This article discusses Soleh as a figure and his philosophical view about the uger, mengku, and megeng, the processes involved in the making of puppet masks. Masks play a central role in the Malangese mask puppet art, but very few studies have discussed the philosophical aspect of the making of puppet masks. The study is based on the data obtained by an interview with Soleh Adi Pramono on 8 February 2019 at Padepokan Mangun Dharmo. Keywords: Malangese Mask Puppet; Puppeter; and Soleh Adi Pramono